KCC2 antagonism and gabaergic synchronization in the entorhinal cortex in the absence of ionotropic glutamatergic receptor signalling. (1st May 2020) - Chen, Li-Yuan; Lévesque, Maxime; Avoli, Massimo
Abstract: γ-Aminobutyric acid (GABA), which is released by interneurons, plays an active role in generating interictal epileptiform spikes during blockade of ionotropic glutamatergic signalling, but it remains unclear whether and how the K + -Cl − cotransporter 2 (KCC2) influences these paroxysmal events. Therefore, we employed tetrode recordings in the in vitro rat entorhinal cortex (EC) to analyze the effects of the KCC2 antagonist VU0463271 on 4-aminopyridine (4AP)-induced interictal spikes that were pharmacologically isolated by applying ionotropic glutamatergic receptor antagonists. After the addition of VU0463271, these interictal spikes continued to occur at similar rates as in control (i.e., during application of 4AP with ionotropic glutamatergic receptor antagonists) but were smaller and shorter. Despite the absence of ionotropic glutamatergic receptor signalling, both interneurons and principal cells increased their firing during interictal spikes. Moreover, we found that KCC2 antagonism increased interneuron firing but decreased principal cell firing during the interictal spike rising phase; in contrast, during the falling phase, interneuron firing decreased in the presence of VU0463271 while no change was observed in principal cell firing. Overall, our results show that KCC2 antagonism enhances interneuron excitability at the onset of interictal spikes generated by the EC neuronal networks during blockade of ionotropic glutamatergic transmission but disrupts later neuronal recruitment. Highlights: We pharmacologically isolated GABAA receptor-mediated interictal spikes induced by 4AP in the rodent entorhinal cortex. Blockade of KCC2 made these interictal spikes smaller and shorter. KCC2 antagonism increased interneuron firing around the onset of interictal spikes. The recruitment of principal cells and interneurons during the interictal spike was disrupted.